PENDIDIKAN KESEHATAN TENTANG PENTINGNYA PEMERIKSAAN KEHAMILAN SESUAI STANDAR SELAMA KEHAMIAN UNTUK OPTIMALISASI 1000 HARI KEHIDUPAN - rafidah; Hapisah; Rusmilawaty; Noor Adha Aprilea; Mellisa; Ulfa Latifah; Noor Zannah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Background: Reducing maternal mortality rate (MMR) and infant mortality rate (IMR) is a major challenge in maternal and perinatal health care. One effective approach to addressing these issues is to improve the quality of delivery assistance provided by trained medical personnel through health care facilities. Standardised prenatal care is a key step in optimising 1000 days of life, where good prenatal care can identify high risks such as anaemia, malnutrition, hypertension, and infection. Objectives: This study aims to increase the knowledge and understanding of pregnant women about the importance of standardised prenatal care during pregnancy to optimise 1000 days of life. The study was conducted at the Bakti Ibu Independent Midwife Service Centre (TPMB) in Murung Kenanga Village, Tanjung Rema Sub-district, Banjar Regency in 2023. Methods: This community service activity was implemented through a health promotion and community empowerment programme with a counseling and Communication, Information, and Education (IEC) approach. Steps include preparation, implementation, and monitoring and evaluation of activities. The population involved in this activity were 15 pregnant women. Results: The evaluation of the activity showed a significant increase in the knowledge of pregnant women regarding the importance of standardised antenatal check-ups. A total of 2 people (13.3%) who had good knowledge in the pre-test increased to 10 people (66.7%) in the post-test. Meanwhile, pregnant women who initially had poor knowledge (86.7% at pre-test) decreased to 5 people (33.3%) at post-test. Conclusion: This increase in knowledge is expected to contribute to improving the quality of maternal and perinatal care, as well as reducing maternal and infant health risks.